Validation study on external wind noise prediction using OpenFOAM / Mohamed Sukri Mat Ali ... [et al.] - Mat Ali, Mohamed Sukri; Shaharuddin, Nur Haziqah; Jalasabri, Jafirdaus; Mohd Sood, Anwar; Mansor, Shuhaimi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Driven by the customer's demand for a low interior noise while keeping the cost of the car to a minimum, the direction for aerodynamic noise reduction is to mitigate its noise source generation. However, the aerodynamic noise generation is complex due to its turbulent nature. This paper presents a validation study in predicting the noise generation due to the turbulent flow near the A-pillar and it's estimated sound level if the sound source is transmitted inside the cabin through the side window glass. The case under study is a generic vehicle model, SAE type 4-fullback body, for its available data to be compared. The noise source is obtained from the numerical simulation using open source CFD packages, OpenFOAM and Curle's equation is used to estimate the sound propagation. The interior sound pressure level is then estimated by assuming sound transmission loss using the law of theoretical frequency for all ranges of noise frequency. A good agreement of the sound pressure level (SPL) between the current calculations and previous experimental measurements are obtained for frequency ranges between 200 Hz to 2000 Hz. The different in the other frequency ranges is mainly due to the invalid assumption when applying the law of theoretical frequency at these typical frequency ranges.